Evolution of EU and its Member States' competitiveness in international trade - Curran, Louise; Zignano, Soledad (Paris, 2009)
"After a long period of domination by the industrialised countries of the North, international trade is today driven by the dynamism of developing countries. This work seeks to analyse how the EU is performing in the light of this emerging competitive threat, by comparing the EU’s export performance on the world market with that of its key competitors between 1995 and 2004. The figures show that the EU has performed particularly well in the more upmarket, expensive and high tech levels of the market. Most notably, Europe is the market leader in up-market products, with almost 31% of the world market in 2004 (versus 20% of the market for all goods). In addition, there is evidence that the EU’s recent enlargement has helped it to maintain a strong performance, thanks to an increasing division of labour within the region. The new member states have become important suppliers of intermediate goods to key EU producers, and in particular German firms, thus becoming increasingly vital to EU competitiveness."